1999
DOI: 10.3109/08916939908994053
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in the Galactosylation of Autoantibodies and Serum IgG in Autoimmune Haemolytic Anaemia

Abstract: A number of systemic autoimmune diseases are associated with increased levels of the agalactosyl (G0) IgG isoforms that lack a terminal galactose from the C(H)2 domain oligosaccharide. The aims were to determine whether there are also persistently high levels of G0 autoantibodies or serum IgG in autoimmune haemolytic anaemia (AIHA), and whether any changes in galactosylation over time are related to the course of disease. Autoantibodies eluted from red blood cells, and serum IgG, were obtained from a patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The ability of the autoantibodies to promote K‐cell‐mediated RBC lysis in an in vitro assay correlated inversely with agalactosyl IgG. Barker et al (1999) studied a patient with autoimmune haemolytic anaemia (AIHA) over 21 months. They found that there were wide fluctuations in galactosylation of the IgG autoantibody, but unfortunately, these seemed to be unrelated to the severity of the haemolytic process, thus it may take a total, or near total, loss of carbohydrate before immune RBC destruction is affected.…”
Section: Mechanisms Of Immune Rbc Destruction (Haemolytic Anaemia)mentioning
confidence: 99%
“…The ability of the autoantibodies to promote K‐cell‐mediated RBC lysis in an in vitro assay correlated inversely with agalactosyl IgG. Barker et al (1999) studied a patient with autoimmune haemolytic anaemia (AIHA) over 21 months. They found that there were wide fluctuations in galactosylation of the IgG autoantibody, but unfortunately, these seemed to be unrelated to the severity of the haemolytic process, thus it may take a total, or near total, loss of carbohydrate before immune RBC destruction is affected.…”
Section: Mechanisms Of Immune Rbc Destruction (Haemolytic Anaemia)mentioning
confidence: 99%
“…Furthermore, it has previously been reported that the Fc glycosylation of rabbit IgG is changed following hyperimmunization [29]. The variations in erythrocyte autoantibody galactosylation between individual NZB mice may re¯ect changes in the level of autoantibody production with time, since similar¯uctuations have also been observed in serial samples taken from a human AIHA patient over several months [27]. These results, together with the current ®nding that the concentration of serum IgG in CBA/Ig b mice inversely correlates with the proportion that is G 0 , lead us to suggest that reduced galactosylation is associated with increased IgG synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…It was not possible to examine the relationship between G 0 autoantibody and haemolysis in the current study, because all the mice killed had only mild anaemia. However, there is no correlation between the severity of disease and the production of G 0 autoantibodies in human AIHA [17,27], indicating that other factors such as the subclass of the autoantibodies, serum IgG concentration and the state of the reticuloendothelial system play a more important role in determining pathogenicity in vivo [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, reduced Fc galactosylation of autoantibodies was observed in AIHA. However, in a time study in a single patient fluctuations in galactosylation did not match disease severity [43]. Changes in Fc galactosylation are still an interesting concept for this autoimmune disease, since in rheumatoid arthritis also reduced galactosylation of total serum IgG was reported that can lead to more lectin pathway activation [44], however, more studies with human anti-RBC autoantibodies are required to say whether it is more than just an interesting concept.…”
Section: Autoantibody Fc Propertiesmentioning
confidence: 98%